Elevated plasma soluble lectin-like oxidised low-density lipoprotein receptor 1 as an independent prognostic biomarker in sepsis - Patricia Mester; Charlotte Birner; Stephan Schmid; Martina Müller; Vlad Pavel; Christa Buechler (Lipids in Health and Disease)
Abstract Background Soluble lectin-like oxidised low-density lipoprotein receptor 1 (sLOX-1) is overproduced during inflammation, with its expression and release triggered by C-reactive protein (CRP). As CRP levels are typically elevated in sepsis, this study aimed to investigate whether sLOX-1 levels increase in parallel. Methods Plasma sLOX-1 levels of 52 patients with systemic inflammatory response syndrome (SIRS), 45 patients with sepsis, 88 patients with septic shock and 37 controls were measured by ELISA. Associations with CRP, underlying diseases, severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) and bacterial infections were analysed. Results Plasma sLOX-1 levels were similarly elevated in patients with SIRS, sepsis, or septic shock compared to controls. Plasma sLOX-1 levels did not differ between male and female controls or patients. Plasma sLOX-1 levels were comparable in patients infected with SARS-CoV-2, Gram-negative bacteria, or Gram-positive bacteria. No association was observed between sLOX-1 levels and underlying liver cirrhosis or pancreatitis. Notably, plasma sLOX-1 levels correlated positively with leukocyte and basophil counts but showed no correlation with CRP or procalcitonin. Of clinical relevance, positive correlations were also found with aspartate aminotransferase (AST) and bilirubin levels. Among the 41 patients who did not survive, sLOX-1, AST, and bilirubin levels were significantly higher compared to those of survivors. Conclusions Plasma levels of sLOX-1 are elevated in patients with SIRS or sepsis and are significantly higher in non-survivors. Of note, they do not correlate with classical inflammatory markers, suggesting that sLOX-1 may function as an independent prognostic biomarker for predicting poor outcomes in patients with SIRS or sepsis.